2018
DOI: 10.1186/s40634-018-0144-6
|View full text |Cite
|
Sign up to set email alerts
|

Numerical comparative study of five currently used implants for high tibial osteotomy: realistic loading including muscle forces versus simplified experimental loading

Abstract: BackgroundMany different fixation devices are used to maintain the correction angle after medial open wedge high tibial osteotomy (MOWHTO). Each device must provide at least sufficient mechanical stability to avoid loss of correction and unwanted fracture of the contralateral cortex until the bone heals. In the present study, the mechanical stability of following different implants was compared: the TomoFix small stature (sm), the TomoFix standard (std), the Contour Lock, the iBalance and the second generation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The study showed that the stress distributions in the HTO‐implants that were obtained in loading conditions (1) and (2) were comparable to one another. The stresses in the implants were all lower than the threshold stress values of each implant material (Diffo Kaze et al 2018). This meant that loading the bone‐implant constructs with physiological loads would not lead to critical stresses that could cause implant damage.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The study showed that the stress distributions in the HTO‐implants that were obtained in loading conditions (1) and (2) were comparable to one another. The stresses in the implants were all lower than the threshold stress values of each implant material (Diffo Kaze et al 2018). This meant that loading the bone‐implant constructs with physiological loads would not lead to critical stresses that could cause implant damage.…”
Section: Discussionmentioning
confidence: 98%
“…(Maas et al 2013; Diffo Kaze et al 2015; Diffo Kaze 2016; Diffo Kaze et al 2017). The loading of the specimens that was considered for the experimental setup corresponded to a realistic loading of the lower limb during the loading response phase of slow walking (Diffo Kaze et al 2018). The key findings of the present study were the following: (1) The FlexitSystem plate showed sufficient strength for static loading, and average fatigue strength was comparable to the previously tested implants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Load simulation was performed in the Simulation Mechanical 2017 software (Autodesk, Inc.). Materials assigned to all parts were considered materials with linear isotropic and elastic mechanical properties and were characterized by Young's modulus and the Poisson's ratio, the values of which are presented in Table I (17)(18)(19).…”
Section: Methods Selection and Load Simulationmentioning
confidence: 99%
“…Materials were considered with linear isotropic, homogeneous and elastic mechanical properties [18,19]. Details of elasticity modulus of bone structure and plate were listed in Table 2, Poisson´s ratios of 0.3 for all three materials [20,21]. In order to simulate the stress of human tibial plateau, the distal tibia was restrained and xed.…”
Section: Boundary Conditions Materials Properties and Loading Force S...mentioning
confidence: 99%